KEPASTIAN HUKUM DALAM PELANGGARAN REGULASI PARQ KAMPUNG RUSIA DI UBUD BALI - Adnantara, Kadek Frediandrika (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2026)
Legal certainty is an important element in the enforcement of regulations, especially in the context of tourism development which often has the potential to violate spatial and environmental rules. The author discusses a case of regulatory violations committed by the Ubud PARQ, known as the "Russian Village," in Ubud, Bali. This violation includes non-compliance with Gianyar Regency Regional Regulation No. 15 of 2015 concerning Public Order and Gianyar Regency Regional Regulation No. 2 of 2022 concerning the Implementation of Risk-Based Licensing. Through a normative research method with a legislative and case approach, this study explores the extent of the application of legal certainty in the settlement of these violations. The results of the study show that the closure of PARQ Ubud operations by the Gianyar Regency Government is a strategic step in enforcing the law, protecting local cultural values, and maintaining environmental sustainability. However, this case also reveals weaknesses in regulatory supervision and coordination between related parties. The study recommends increased surveillance, regulatory harmonization, and consistent law enforcement to ensure the sustainability of tourism governance in Bali.